Beneficial effect of ticagrelor on microvascular perfusion in patients with ST-segment elevation myocardial infarction undergoing a primary percutaneous coronary intervention. Issue 5 (August 2019) - Wang, Xuechao; Li, Xinning; Wu, Haibo; Li, Ruyi; Liu, Huiliang; Wang, Lili; Bai, Shiru; Zhang, Lina; Chen, Tianlei; Liu, Jia; Li, Qi; Du, Rongpin
Abstract : Background: Ticagrelor significantly reduced the incidence of death, myocardial infarction, and stent thrombosis in patients with ST-segment elevation myocardial infarction (STEMI) intended for reperfusion with a primary percutaneous coronary intervention (pPCI). However, the effects of this drug on microvascular perfusion in patients presenting with STEMI have not been evaluated completely. Patients and methods: A total of 298 patients presenting with STEMI were randomized to either ticagrelor 180 mg loading, followed by 90 mg twice daily, or clopidogrel 600 mg loading, followed by 75 mg daily. The primary endpoint was ST-segment resolution at 90 min after pPCI. The secondary endpoints included myocardial blush grade and corrected thrombolysis in myocardial infarction frame count after the procedure. Left ventricular ejection fraction and major adverse cardiac events (MACE) at the 1- and 6-month follow-up time points were also recorded. Results: There were no significant differences between the two groups with respect to baseline characteristics. Ticagrelor administration resulted in a higher rate of completed ST-segment resolution (58.67 vs. 39.86%, P =0.001), higher myocardial blush grade (2.63±0.64 vs. 2.41±0.71, P =0.005), and lower corrected thrombolysis in myocardial infarction frame count (19.68±7.38 vs. 22.35±8.30, P =0.004). At 6 months, left ventricular ejection fraction was higher (55.01±8.44 vs. 52.34±9.05%, P =0.009) in the ticagrelor group. Kaplan–Meier analysis showed that MACE-free survival had also improved in the ticagrelor group during the 1- and 6-month follow-up time points. Conclusion: Compared with clopidogrel, ticagrelor improves myocardial perfusion and left ventricular ejection fraction, and reduces the incidence of MACE for STEMI patients undergoing pPCI, with no significant increase in major bleeding.